PERTUMBUHAN JAMUR PADA MEDIA BIJI KLUWIH DAN BIJINANGKA SEBAGAI SUBSTITUSI MEDIA PDA - RAHMAWATI, RESTI, Triastuti Rahayu, S. Si, M. Si (2016)
THE GROWTH OF FUNGUS IN KLUWIH AND NANGKA SEEDS MEDIA AS A SUBSTITUTION PDA MEDIA. Resti Rahmawati, A420120048, Department of Biology Education, School of Teacher Training and Education, Muhammadiyah University of Surakarta, March, XVI+32 ABSTRACT PDA is the most media to grow the fungus, but the price of this media is expensive so it need an alternative media that easy and cheap to get it. This study aims to determine the growth of Aspergillus niger in alternative kluwih and nangka seeds media. This research was an experimental study using a completely randomized design (CRD) one factor was the type of media is PDA (M0), kluwih seed media (M1), nangka seed media (M2) and using the test fungus A. niger (J1). Inoculation of A. niger used agar block method for 3 days with a temperature of 28⁰C. Parameter of research was colony diameter and sporulation of A. niger. Data were analyzed with descriptive qualitative methods. The result of this research showed that the best growth for Aspergillus niger was after 72 hours incubation, colony diameter continually in PDA media, kluwih seed media, nangka seed media is 4,7 cm, 4,3 cm, 4,1 cm with heavy sporulation. So, the conclution is that kluwih and nangka seeds media can be use as a substitution of PDA media for the growth of fungus. Keyword : kluwih and nangka seeds, Aspergillus niger, PDA.